Isto não é uma cópia de This is not a copy - Ministro, Bruno (MATLIT: Materialities of Literature, 2019)
Recensão crítica de Kaja Marczewska, This Is Not a Copy: Writing at the Iterative Turn. New York/London: Bloomsbury Academic, 2018. 303 pp. ISBN: 978-1-5013-3783-3. DOI: https://doi.org/10.14195/2182-8830_7-1_17